Brave new Bollywood : in conversation with contemporary Hindi filmmakers - Nirmal Kumar, 1964-; Chaturvedi, Preeti (SAGE Publications, 2015)
This book examines filmmakers in India, their religious beliefs, social moorings, cinematic influences, attitudes towards filmmaking and experiences of making movies.--Publisher's description.
Keywords: Motion picture producers and directors -- India -- Interviews.; Motion pictures -- India.; Motion pictures -- Production and direction -- India.; Producteurs et réalisateurs de cinéma -- Inde -- Entretiens.; Cinéma -- Inde.; Cinéma -- Production et réalisation -- Inde.; PERFORMING ARTS -- Reference.; Motion picture producers and directors; Motion pictures; Motion pictures -- Production and direction; India; Interviews; Interviews.